PENDEKATAN RULE OF REASON DALAM PRAKTIK DISKRIMINASI PADA PUTUSAN KPPU TAHUN 2020: Rule Of Reason Approach To Discrimination Practices In The 2020 KPPU Decisions - Mardohar, Joice Chintya; Anggraini, Anna Maria Tri (Faculty of Law, Universitas Trisakti, 2024)
Discriminatory practices are common in business competition and this is not prohibited as long as it does not lead to unfair business competition. The thesis discusses 3 (three) KPPU decisions in 2020 regarding allegations of discriminatory practices committed by business actors. The main problem in this thesis is how the actions of business actors can fulfill the element of violation and how to apply the rule of reason approach in Article 19 point d of Law Number 5 of 1999 in the 2020 KPPU Decisions. This thesis is a normative descriptive using secondary data in the form of journals or books and primary data in the form of interviews with KPPU and data processing is carried out qualitatively, and conclusions are drawn using deductive logic. The conclusion from this study is that discriminatory acts cause obstacles in vertical business relations and are in the relevant market which are different but interrelated and often occur in the essential facilities sector. Discriminatory practices can occur effectively if the KPPU's business actors use the application of the rule of reason in handling the case, in which the result is that discriminatory practices can only run effectively if the business actors are in the position of highest market control.